The Impact of Artificial Intelligence and Work Training on Human Resource Performance: A Case Study of PT Satria Bahana Sarana - Firna Shizuka Nugroho; Btari Mariska Purwaamijaya; Adi Prehanto (Eduvest - Journal of Universal Studies, 2025)
This study aims to analyze the influence of artificial intelligence (AI) and work training on human resource performance at PT Satria Bahana Sarana (SBS). The research employed a quantitative approach with data collection conducted through questionnaires distributed to 165 office employees as respondents. Data analysis was performed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) to test the research hypotheses. The findings indicate that artificial intelligence has a significant and positive effect on HR performance with a path coefficient of 0.47 (p < 0.01), suggesting enhanced efficiency and productivity in the workplace. Work training also contributes positively and significantly with a path coefficient of 0.38 (p < 0.01), where structured training programs prove to improve employee competencies and facilitate the achievement of organizational objectives. The research model yielded an R-square value of 0.622, indicating that artificial intelligence and work training collectively explain 62.2% of the variance in HR performance, while the remaining 37.8% is influenced by variables outside the model. This study highlights the crucial role of AI integration and comprehensive work training programs as key strategies for optimizing employee performance in the era of digital transformation.